Disquiets over old, always contemporary, subjects in health - Paula Borges Jacques; Querubina Bringel Olinda (Universidade de Fortaleza, 2013)
The Brazilian Journal in Health Promotion (Revista Brasileira em Promoçãoda Saúde - RBPS), throughout its course, writes a history of evolution, seeking to improve the quality of its information. This is the aim of a scientific information vehicle: to accomplish its mission of diffusing.In this issue, RBPS attracts the reader with subjects focused on the areas of nutrition, physical exercise, worker health and infectious diseases, such as leprosy and tuberculosis. Those are very well-known diseases in public health, due to the existence, in the past, of vertical programs and horizontal actions, such as the implementation of the Unified and Decentralized Health System (Sistema Unificado e Descentralizado de Saúde - SUDS), followed by the Unified Health System (Sistema Único de Saúde - SUS). Further modifications were performed on the public health system, determined by the Constitution of 1988(¹).RBPS also brings, in this issue, an article on dengue, an infectious, febrile and acute disease, with benign and serious cases, caused by an arbovirus of the Flavivirus genus that, in an endemic spatial acquaintanceship for decades, has presented several epidemic years in Brazil, with four known serotypes: DENV-1, DENV-2, DENV-3 e DENV-4(²). The Journal also includes an article on the osteomuscular discomfort, health in the penitentiaries, the hypertension patient's adherence to treatment and women with HIV. It is therefore well diversified, with important contents to the scientific community and attractive to the health services.In this editorial, two subjects are picked out for the reader's reflection: tuberculosis and nutrition.Tuberculosis, which had its bacillus identified by Robert Koch in 1882(³), has been studied for decades in Brazil. The Ministry of Health has acquired a praiseworthy experience in prevention and control of infectious diseases. However, it is worth questioning what has happened to the extensive experience brought by the Tuberculosis Prevention and Control Programme. In the 1970s, the programme was decentralized and integrated to the state and municipal health services. Later on, it was incorporated to the Family Health Programme (Programa de Saúde da Família) and to the Community Health Agents (Agentes Comunitários de Saúde).It is known that the disease registered from 2005 and 2010, only in the Brazilian capitals, around 44,864,500 cases/year and an incidence rate around 59 cases per 100,000 inhabitants(4). In its historical retrospective, prior to SUS, the disease was confronted on the basis of the epidemiological surveillance, with calculated incidence rate, healing percentage and actions to detect, notify, investigate, confirm and treat the cases, besides reducing the abandonment of the treatment, thereby reaching good healing results. There was a permanently sustained action, organized and with systematic evaluations in the states and by regions.Tuberculosis has a lived and learned history in the primary network; its past should be examined and enhanced, never forgotten, so that people might get rid of such harm, not only in Brazil, as in the world. A few years ago, the World Health Organization (WHO), along with the participants of many countries andnon-governmental organizations, implemented the movement Stop TB(5), which intends to catch the interest of world leaders for the prevention, control and cure of the disease. Its most recent global plan(6) presents goals for the period from 2011 to 2015. The movement started in 2000 with a big dream:to avoid the spread of tuberculosis throughout the world, eliminating it.It occurs diversely among poor and rich people, in different urban spots, city districts, slums and sociallyclosed environments, like the penitentiaries. Professionals of the area are also aware of the existence of related factors, such as the infection by HIV, malnutrition and alcoholism. However, the necessary and indispensable requisite for it to be transmitted is the existence of the bacillus in circulation,sensitive to sunlight, anaerobic and with predilection for the lungs.Will tuberculosis become more spread? Will the new cases increase? What about the incidence in the poor urban communities, in the capitals, mainly the ones in the Northeast? Health is the disposal of many of the complex problems and trampling of public policies, and the RBPS represents the many aspirations of the area in search for effective service improvement.The second theme picked for thinking in this issue of RBPS is the matter of overweight and obesity among the Brazilian population, including young adults, adolescents and children. Brazil took so long to wake up for a feeding education policy(7). The advertising of school meal in the public schools focusing on the number of meals/day an attraction for the student seems to exceed the disclosure of the educational quality, which is the primary and nontransferable object of schools.The feeding of children and youngsters is on the wrong side of the dietary legislation on quantity, quality, harmony and suitability of food(8). That's what the Brazilian statistics show (7,9,10). Improper and abusive feeding leads to bad habit (9) and, afterwards, to food addiction. When sedentary lifestyle, so much in vogue, comes along, health suffers the consequences, with the early onset of chronic diseases. It is time to review the public policies and its strategies, bringing from WHO(11) to the Primary Care Units the spaceof physical exercises practice with qualified professionals, thereby addressing excess weight, promoting the formation of healthy habit and assisting in sociability. That would, without any doubt, help reducing the loneliness and depression of the modern world.Health is always present in comments on the television and in the press. This sector takes the effects of problems related to food shortage, exposure to weather factors, deficiencies in the national policy on public safety and drug control, of lack of sports in the health care units and so many other problems we daily confront.Those who neglect the actions of health promotion and disease prevention spend much more with treatmentand rehabilitation. The treatment complextiy for chronic diseases is much higher than for the infections ones, since the first have multiple causes and involve more diagnostic equipment and medicine, used by the patient for long periods and, sometimes, forever.Attuned to the news and the scientific truth, RBPS seeks to represent the expectations in the health area and this issue, once more, encompasses what is desired.REFERENCES1. Brasil. Constituição da República Federativa do Brasil.2. Brasil, Ministério da Saúde, Secretaria de Vigilância emSaúde - departamento de Vigilância Epidemiológica.Doenças Infecciosas e Parasitárias: guia de bolso. 8ª.ed. revisada. 2010.3. Brasil. Ministério da Saúde. Fundação Nacionalde Saúde. Sociedade Brasileira de Pneumologia eTisiologia. Controle da Tuberculose: uma proposta deintegração ensino-serviço. 5ª. ed. FUNASA, 2000.4. http://tabnet.datasus.gov.br em 5/04/2013.5. WHO. Tuberculosis (TB). Stop TB Partnership. Theglobal plan to stop TB. In: http://www.stoptb.org/about/ acesso em 29 de março de 2013.6. The global plan to stop TB 2011-2015. WHO. http://www.stoptb.org/assets/documents/global/plan/TB_GlobalPlanToStopTB2011-2015.pdf acesso em 29março de 2013.7. Brasil. Ministério da Saúde. Política nacional dealimentação e nutrição. Brasília: Ministério da Saúde;2000.8. Vitolo, MR. Bortolini, GA. Feldens, CA. Impactoda implementação dos dez passos da alimentaçãosaudável para crianças: ensaio de campo randomizado.Cad. Saúde Pública, Rio de Janeiro, 21(5):1448-1457,set-out, 2005.9. Silva Santos, LA. Educação alimentar e nutricionalno contexto da promoção de práticas alimentaressaudáveis. Rev. Nutr., 18(5):681-692, set./out., 200510. Brasil. II Conferência Nacional de Segurança Alimentare Nutricional: A construção da Política Nacional deSegurança Alimentar. Relatório final. maio 2004.Disponível em http://www.fomezero.gov.br acesso em28 de março de 201311. Organização Mundial da Saúde. Documento preliminarpara a "Estratégia Global em Dieta, Atividade Físicae Saúde.